Pengaruh Bauran Pemasaran (Marketing Mix) Terhadap Kinerja Penjualan Jasa Tour Pada Biro Perjalanan Mega Wisata Palembang - Zein Ghozali; Munyati; Tutik Pebrianti; Indah Mawarni; Vivin Afini (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2020)
This research was conducted to find an overview of the influence of the marketing mix on the sales performance of the Palembang Mega Wisata Travel Bureau. The method used in this study is causal. The number of samples in this study were 50 customers who used the services of the Palembang Mega Wisata Travel Bureau. Data collection techniques by distributing questionnaires.In this study there are two groups of variables. The group is an independent variable consisting of product (X1), price (X2), promotion (X3), place (X4), people (X5), process (X6) and physical facilities (X7) variables. While the dependent variable is the sales performance of the Mega Wisata Palembang Travel Bureau. This study aims to see the influence of the marketing mix on the sales performance of the Palembang Mega Wisata Travel Bureau To measure the relationship between variables used multiple linear regression analysis. In accordance with the results of the regression analysis, it turns out that together all marketing mix variables have an influence on the sales performance of the Mega Wisata Palembang Travel Bureau. Partially the process variable has the most dominant influence on the sales performance of the Palembang Mega Wisata Travel Bureau